Chemical Composition of Salvia aratocensis Extract obtained by Supercritical Fluid Extraction and its Antigenotoxicity against Ultraviolet Radiation-Induced DNA Damage (2015)
Salvia is a cosmopolitan and important genus, widely used in flavoring and traditional medicine for treatments of respiratory and gastrointestinal diseases. The present work evaluated the chemical composition of Salvia aratocensis extract obtained by supercritical CO2 extraction, as well as its DNA protective effect against ultraviolet radiation (UVR)-induced genotoxicity. S. aratocensis extract composition was determined by gas chromatography-mass spectrometry (GCMS). The antigenotoxic effect of S. aratocensis extract was assayed in co-incubation procedures using the SOS chromotest in Escherichia coli PQ37 cells. The major components of the plant extract were α-cadinol (31.8%), 1,10-epi-cubenol (12.9%), trans-β-caryophyllene (7.7%), -cadinene (6.6%), and squalene (6.5%). S. aratocensis extract protected bacterial cells against UVR-induced genotoxicity at doses between 0.063 and 1 mg/mL. The results were discussed in relation to the DNA protective potential of the S. aratocensis extract and its major constituents.